Competency Index of Technical Vocational Education and Training (TVET) Instructors for 4.0 Industrial Revolution - Shahroni, Nuraini; Minghat, Asnul Dahar; Mustakim, Siti Salina Binti (ASEAN Journal of Educational Research and Technology, 2022)
The purpose of this research is to develop the Competency Index of TVET instructors towards Industrial Revolution 4.0 (IR4.0). The new technological waves from IR4.0 bring changes and development to current technology, and the TVET education system in Malaysia is bound to face a similar fate. TVET instructors play the biggest role to shape the human product in TVET institutions. A competent TVET instructor will yield competent human capital. Therefore, the reinforcement of the TVET system should begin with the main player which is the TVET instructor.  Therefore, a Delphi study will be conducted involving 11 expert panels to identify the index of Competency of TVET instructors towards IR4.0. With the findings from this Delphi study, a questionnaire about Competency Index will be developed. Then, the questionnaire will be distributed to 147 TVET instructors from the electrical and electronics department at the institution under the Ministry of Youth and Sport. The data collected from the questionnaire will help the researcher to develop the Competency Index of TVET instructors towards IR4.0. The findings of the study will help the TVET institution in preparing TVET instructors to become specialized, highly-skilled, competent, and efficient in the attempt to strengthen the teaching profession, which is in line with IR4.0.